2015
DOI: 10.1155/2015/781973
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Iron-Folate Supplement and Associated Factors among Antenatal Care Attendant Mothers in Misha District, South Ethiopia: Community Based Cross-Sectional Study

Abstract: Background. In Ethiopia, higher proportions of pregnant women are anemic. Despite the efforts to reduce iron deficiency anemia during pregnancy, only few women took an iron supplement as recommended. Thus, this study aimed to assess compliance with iron-folate supplement and associated factors among antenatal care attendant mothers in Misha district, South Ethiopia. Method. Community based cross-sectional study supported with in-depth interview was conducted from March 1 to March 30, 2015. The sample size was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
62
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 14 publications
27
62
8
1
Order By: Relevance
“…There is similarity of compliance pattern among the two counties despite their cultural and demographic diversity. These findings are consistent with reports on IFAS from similar rural settings in low and medium income countries (LMIC) notably, Pakistan (38.3%), South Ethiopia (39.2%) [ 35 ] and Western Ethiopia (20.4%) [ 36 ]. Despite efforts to promote IFAS, the finding could be attributed to the fact that compliance with medical advice depends on patients’ rational decision-making about the costs and benefits of prescribed actions, depending upon individual socio-cultural circumstances.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There is similarity of compliance pattern among the two counties despite their cultural and demographic diversity. These findings are consistent with reports on IFAS from similar rural settings in low and medium income countries (LMIC) notably, Pakistan (38.3%), South Ethiopia (39.2%) [ 35 ] and Western Ethiopia (20.4%) [ 36 ]. Despite efforts to promote IFAS, the finding could be attributed to the fact that compliance with medical advice depends on patients’ rational decision-making about the costs and benefits of prescribed actions, depending upon individual socio-cultural circumstances.…”
Section: Discussionsupporting
confidence: 91%
“…The IFAS compliance status was defined as the number of IFAS tablets taken in the preceding 7 days (1 week). Pregnant mothers who took at least 70% of the expected dose of the IFAS tablets in the week preceding the interview, an equivalent of five tablets per week, were considered compliant with IFAS [ 21 , 35 ]. Conversely the respondents who took less than five IFAS tablets were considered as non-compliant.…”
Section: Methodsmentioning
confidence: 99%
“…These findings were similar to a coverage of 67% reported in urban Nairobi County [40] in Kenya and 64.7% reported in India [41] respectively. However, the findings were higher than reports on IFAS coverage from low and medium income countries (LMIC) with similar rural settings namely, South Ethiopia (39.2%), Pakistan (38.3%), [38], Nigeria (37.5%) [42] and Western Ethiopia (20.4%) [20]. Nevertheless, lower coverage (18%) has been reported in a neighbouring County of Machakos, Kenya [43].…”
Section: Discussioncontrasting
confidence: 63%
“…This study showed increased awareness on IFAS side effects in both groups. Studies have shown that accompanying health education with clear instructions on intake of IFAS substantially improves compliance [38,44]. This is demonstrated in another Kenyan study where advice by health workers was independently associated with higher compliance [37,45].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation